Accuracy evaluation of partially guided and fully guided templates applied to implant surgery of anterior teeth: A randomized controlled trial. (2nd February 2021) - Lou, Fangzhi; Rao, Pengcheng; Zhang, Maorui; Luo, Shihong; Lu, Shi; Xiao, Jingang
Abstract: Objectives: To study the accuracy of partially guided and fully guided templates applied to implant surgery of anterior teeth. Materials and methods: Sixty patients who were scheduled to receive dental implant treatment in the anterior region were enrolled and randomly assigned to one of the following study groups ( n = 20 each): routine implant‐supported restoration treatment (control group, 30 implants), implant‐supported restoration treatment using a partially guided template (test group 1, 36 implants), and implant‐supported restoration treatment using a fully guided template (test group 2, 33 implants). The depth of implant was controlled for fully guided template. After implantation, planned implants and placed implants were superimposed using digital software, and the deviations (angular, coronal, apical, depth) were analyzed. Esthetic parameters were assessed at baseline, 6 months, and 1 year after the final restoration. Pink esthetic score (PES) and white esthetic score (WES) were respectively used to evaluate the soft tissue and restoration esthetic outcome. Each parameter of PES and WES is assessed with a 0–1‐2 score with 2 being the best and 0 being the worst score. Results: There were significant differences in all of the deviation parameters between the control group, test group 1, and test group 2 ( p  < 0.001). Mean angular, coronal, apical and depth deviations were all the highest in the control group (6.61 ± 1.09°, 1.05 ± 0.17 mm, 1.36 ± 0.13 mm, and 1.02 ± 0.13 mm, respectively), and lowest in test group 2 (2.05 ± 0.45°, 0.39 ± 0.12 mm, 0.28 ± 0.09 mm, and 0.24 ± 0.06 mm, respectively). At 1 year after the final restoration, the analysis revealed mean PES values of 7.09 ± 0.56 (control group), 8.39 ± 0.54 (test group 1), and 9.04 ± 0.35 (test group 2). The WES values were 7.24 ± 0.54 (control group), 8.47 ± 0.44 (test group 1), and 8.97 ± 0.38 (test group 2). At all examinations, the mean PES and WES values were both the highest in test group 2 and lowest in the control group. The PES and WES values recorded in the control group at baseline, 6 months, and 1 year after final restoration were significantly lower than those in test groups ( p  < 0.001). Moreover, the PES and WES values recorded in the test group 1 at baseline, 6 months, and 1 year after final restoration were significantly lower than those in test group 2 ( p  < 0.05). Conclusions: Digital surgical guides can improve the accuracy of the three‐dimensional position of implants in the maxillary esthetic zone, the fully guided template has higher precision than that of the partially guided template, and plays an important role in obtaining the ideal esthetic outcome for maxillary anterior teeth.